2014
DOI: 10.4103/0974-777x.145234
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi-Fujimoto disease: Clinical and laboratory characteristics and outcome

Abstract: Introduction:Kikuchi-Fujimoto disease is an uncommon disorder with worldwide distribution, characterized by fever and benign enlargement of the lymph nodes, primarily affecting young adults. Awareness about this disorder may help prevent misdiagnosis and inappropriate investigations and treatment. The objective of the study was to evaluate the clinical and laboratory characteristics of histopathologically confirmed cases of Kikuchi's disease from a tertiary care center in southern India.Materials and Methods:R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
3
16
0
Order By: Relevance
“…Anemia was defined as having a hemoglobin level lower than 12 g/dL. [11] Thrombocytopenia was defined as a platelet count below 150,000 cells/μL. [19] Elevated ESR was defined as a level exceeding 60 mm/h.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anemia was defined as having a hemoglobin level lower than 12 g/dL. [11] Thrombocytopenia was defined as a platelet count below 150,000 cells/μL. [19] Elevated ESR was defined as a level exceeding 60 mm/h.…”
Section: Methodsmentioning
confidence: 99%
“…[19] Elevated ESR was defined as a level exceeding 60 mm/h. [11] Elevated CRP was defined as a level exceeding 8 mg/L. [11] An abnormal LFT was defined as an alanine aminotransferase level exceeding 40 IU/L.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathological findings include paracortical expansion with foci of coagulative necrosis and extensive karyorrhectic debris. 6 Several studies have shown CD8+ T lymphocytes and plasmacytoid dendritic cells as the predominant proliferating cells with a relative absence of neutrophils. 3,6,7 There are currently no treatment guidelines for KFD although spontaneous resolution typically occurs in one to six months with a low recurrence rate of 3-4%.…”
Section: Case Reportmentioning
confidence: 99%
“…6 Several studies have shown CD8+ T lymphocytes and plasmacytoid dendritic cells as the predominant proliferating cells with a relative absence of neutrophils. 3,6,7 There are currently no treatment guidelines for KFD although spontaneous resolution typically occurs in one to six months with a low recurrence rate of 3-4%. 1,3,7 Due to its underlying inflammatory response, non-steroidal antiinflammatory drugs and antipyretics are important for symptomatic relief.…”
Section: Case Reportmentioning
confidence: 99%